FAKTOR-FAKTOR YANG MEMPENGARUHI KECEPATAN ADOPSI TEKNOLOGI PENGELOLAAN TANAMAN TERPADU PADI SAWAH (Oryza sativa L.) - Samsudin Samsudin; Sugeng Widodo; Achdiyat Achdiyat (Politeknik Pembangunan Pertanian Bogor, 2020)
The research was conducted from October to December 2011. The aim is to determine the level of application of the technology components of rice integrated crop management and the factors that affect the speed of technology adoption of integrated crop management of rice paddies in the village of Tegal regency Jatinegara Luwijawa District. The results showed that application of research of basic technology components in lowland rice PTT is still weak, namely: the provision of organic matter, plant population regulation through legowo row cropping systems, site-specific fertilization, and control of the IPM approach. While the application of component technology of choice, which is weak at: planting seeds 1-3 stems/clump, and planting young seedlings<21 days after seedling. The factors that affect the speed of technology adoption of integrated rice crop management is strongly influenced by the simultaneous perception of innovation characteristics (relative advantage, compatibility, complexity, triabilitas, and observabilitas), and PTT paddy promotional activities undertaken by the officer/extension. However, partially, not all of these factors significantly affect the speed of technology adoption PTT rice.